2018
DOI: 10.3892/ol.2018.9880
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of SNHG12 suppresses tumor metastasis and epithelial‑mesenchymal transition via the Slug/ZEB2 signaling pathway by targeting miR‑218 in NSCLC

Abstract: Non-small cell lung cancer (NSCLC) is a type of lung cancer which has a high mortality and low survival rate. Previous studies have revealed that long non-coding RNAs participate in tumorigenesis and metastasis in NSCLC. In the present study, the function of small nucleolar RNA host gene 12 (SNHG12) was investigated in NSCLC. Using reverse transcription-quantitative polymerase chain reaction analysis, it was identified that SNHG12 was significantly overexpressed in NSCLC specimens. Furthermore, overexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 35 publications
4
56
0
Order By: Relevance
“…There is evidence that lncRNAs can act as molecular scaffolds, sponges or coactivators in tumor scaffolds by interacting with DNA, RNA or proteins [5,31,32] . At present, increasing evidence has shown that the abnormally high expression of SNHG12 plays a carcinogenic role in various malignant tumors [10][11][12][13][14][15][16][17][18][19][26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence that lncRNAs can act as molecular scaffolds, sponges or coactivators in tumor scaffolds by interacting with DNA, RNA or proteins [5,31,32] . At present, increasing evidence has shown that the abnormally high expression of SNHG12 plays a carcinogenic role in various malignant tumors [10][11][12][13][14][15][16][17][18][19][26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al found that inhibition of the SNHG12-miR-195-SOX5 axis signi cantly obstructs the malignant biological behavior of glioma cells [11] . Sun et al noted that lncRNA SNHG12 accelerates the deterioration of patients with ovarian cancer by upregulating SOX4 [12] . Therefore, whether SNHG12 is a biomarker for the detection and treatment of tumors is a growing concern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been revealed that miR-218 negatively regulated the IL-6 receptor and JAK3 gene expression in lung cancer cells by directly targeting their 3 -UTR regions, thereby repressing tumor sphere formation and other tumorigenesis features [81]. Another study showed that administration of miR-218-mimic downregulated the expression of Slug and ZEB2 in lung cancer cells [82], but the detailed mechanism still remains unclear. In OSCC, HPV E6-mediated paxillin expression has been shown to promote colony formation and invasion in oral cancer via decreasing miR-218 [83].…”
Section: Microrna-218mentioning
confidence: 99%
“…Reduced E-cadherin expression has been shown to be associated with poorly differentiated and metastatic NSCLC. In NSCLC, knockdown of SNHG12 suppresses tumor metastasis and epithelial-mesenchymal transition via the Snail2/ ZEB2 signaling pathway by targeting miR-218 [10]. It has been reported that NatD promotes lung cancer progression by preventing histone H4 serine phosphorylation to activate Snail2 expression [11].…”
Section: Introductionmentioning
confidence: 99%